The value of Jirgl's flocculation test in the diagnosis of jaundice - Bell, Joyce L. (1964)
Jirgl's serum flocculation reaction was examined in a series of 121 patients with varying types of liver disease. Positive results were found in 90% of patients with proven extrahepatic obstructive jaundice. Strongly positive reactions were also obtained in primary biliary cirrhosis and chlorpromazine jaundice. One out of three cases of `cholestatic' hepatitis gave a weakly positive reaction and the test may be of value in the diagnosis of this condition and in the rare recurrent conjugated hyperbilirubinaemia in which it is also negative. Eighty-four per cent of cases of portal cirrhosis were negative and the finding of a positive result in this condition may indicate the presence of a hepatoma. No correlation could be found either in intra- or extrahepatic obstructive jaundice between the degree of flocculation present and the severity of the obstruction as judged by serum bilirubin and alkaline phosphatase levels.